Research-based companies perform better - Alexander Eickelpasch (DIW Economic Bulletin, 2012)
The past ten years have seen an expansion in industrial research. There has been a significant increase in the number of research-based companies, as well as in employment in research and development, and in expenditure in this area. Growth has been observed predominantly in companies in less research-intensive sectors and in small and medium-sized enterprises. Consequently, over the last decade, industrial research in Germany has become more widespread. There has been steady growth in the contribution made by research-based companies to total manufacturing output and to employment. Moreover, these companies are considerably more efficient than non-research-based companies-in terms of per capita productivity-and have increased their lead over the course of time. Political support may have also been a contributing factor to the expansion of research and development, particularly in medium-sized industrial enterprises.
Keywords: O31; L60; D24; 330; research and development; manufacturing; labor productivity